2021
DOI: 10.3390/catal11080970
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conversion of Flax Shives in Sub- and Supercritical Ethanol in the Presence of Ru/C Catalyst

Abstract: Thermal conversion of flax shives was studied in sub- and supercritical ethanol medium at 225 and 250 °C in the presence of the bifunctional catalyst 3% Ru/C. The use of 3% Ru/C catalyst in the process of thermal conversion of flax shives in supercritical ethanol was found to increase the conversion of the shives by 27% and the yield of liquid products by 10%. The use of 3% Ru/C catalyst in sub- and supercritical ethanol led to the destruction of both lignin and cellulose. The degree of delignification in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The scientific community is constantly on the lookout to find alternative energy sources due to the trend in decreasing fossil energy consumption and increasing environmental pollution [ 1 , 2 , 3 ]. Researchers have been very interested in biomass resources due to their green, renewable, and clean attributes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific community is constantly on the lookout to find alternative energy sources due to the trend in decreasing fossil energy consumption and increasing environmental pollution [ 1 , 2 , 3 ]. Researchers have been very interested in biomass resources due to their green, renewable, and clean attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been very interested in biomass resources due to their green, renewable, and clean attributes. Lignin is a component of biomass resources that contains aromatic rings [ 1 , 2 , 3 ]. Lignin has versatile applications in many areas, including chemical engineering, materials, and food.…”
Section: Introductionmentioning
confidence: 99%
“…The model of a circular economy and the European Union's policy on biomass energy use are parts of the overall research and technological development strategy in Europe. Intensive research and development work is focused on new methods of processing biomass into components for motor fuels and chemicals [1][2][3][4][5][6]. Biogas, which is a by-product of the biological decomposition of organic substances under anaerobic conditions, belongs to the important renewable energy sources (RES) [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Two articles of the Issue are devoted to the study of processing agricultural waste, flax shives, by hydrogenation methods [8,9]. Thermal conversion of flax shives in ethanol with and without molecular hydrogen was studied in the presence of the bifunctional ruthenium catalyst on carbon support.…”
mentioning
confidence: 99%
“…Analysis of the molecular weight distribution of liquid products showed that using the catalyst, as well as molecular hydrogen, leads to shifting the molecular weight distribution towards low molecular weight products. The most promising individual compound of the process is guaiacylpropane [8,9].…”
mentioning
confidence: 99%